(untitled) (Research, Society and Development, 2021)
An outbreak of the new coronavirus (COVID-19) started in December 2019, and spread throughout China, spreading to the world in a short time, which requires immediate searches for its treatment. Thus, the use of chloroquine (CQ) and hydroxychloroquine (HCQ) has aroused interest in COVID-19. This systematic review follows the reporting items indicated for systematic reviews and Meta-Analysis Guidelines (PRISMA). The descriptors were selected: “SARS-CoV-2”, “COVID-19”, “Hydroxychloroquine” and “Chloroquine” and included in the databases Science Direct, United States National Library of Medicine (PubMed), Latin American bibliographic information on health sciences (LILACS), Scientific Electronic Library Online (SciELO) and Web of Science to search for studies. After screening, a total of 6.339 studies were found. After reading and applying the eligibility criteria, a total of 8 articles were selected to prepare the outcomes of this review. The results of the studies showed that the use of HCQ has outcomes with no significant improvement in the clinical picture, including association with adverse events (including serious) in patients with COVID-19. Thus, randomized clinical trials did not provide evidence of the efficacy of HCQ in patients with COVID-19, showing that an HCQ is not significantly effective, and has negative results regarding its safety for patients with COVID-19.